Parametrial endometriosis: A predictive and prognostic factor for voiding dysfunction and complications. (September 2022) - Benoit, Louise; Dabi, Yohann; Bazot, Marc; Thomassin-Naggara, Isabelle; Ferrier, Clément; Puchar, Anne; Owen, Clémentine; Touboul, Cyril; Darai, Emile; Bendifallah, Sofiane
Highlights: We studied morbidity associated with parametrectomy during surgery for endometriosis. Parametrial involvement (PI) increased postoperative complications and dysuria. Parametrectomy was the resection most associated with complications. A consensual definition and preoperative identification of PI is needed. Abstract: Objective: Parametrial involvement (PI) in endometriosis is poorly defined resulting in an underestimation of its impact during surgical excision. The aim of our study was to assess the surgical complications associated with parametrectomy during surgery for endometriosis. Our secondary objective was to compare the surgical complications rates of a parametrectomy to the excision of other deep pelvic endometriotic locations. Study design: Patients who underwent surgery for deep pelvic endometriosis from 2013 to 2018 in a French referral center were retrospectively included. Surgical complications were assessed according to whether a parametrectomy had been performed. The extent of surgery (colpectomy, torus, utero-sacral (USL) and/or rectal resection) was also assessed. Voiding dysfunction was defined as the need for self-catheterization ≥1 month and intra and postoperative complications were graded using the Clavien-Dindo classification (CDC). Results: We included 753 patients: 285 (37.8 %) with PI. Patients with PI had higher ASRM scores and more extensive surgery than those without. These patients also had higher rates of voiding dysfunctions (17.5 % versus 8.98 %, p < 0.01), and postoperative complications (44.6 % versus 24.6 %, p < 0.01), including major complications (CDC 3–4) (14.7 % vs 8.5 %, p = 0.01). The extent of the surgical resection of endometriosis was strongly associated with surgical complications after multivariable analysis, and the addition of a parametrectomy during surgery greatly increased rates of adverse postoperative events. Voiding dysfunction was frequent in women with combined resection of the torus, utero-sacral ligaments, parametrium and vagina (adjusted OR = 37.28, 95 %CI = 6.84–203.11, p < 0.01, reference: resection of the USL). Conclusion: Parametrectomy significantly impacts postoperative complications in patients undergoing surgery for endometriosis.